Faktor Penghambat Peran Penyidik Polres Lampung Utara Terhadap Tindak Pidana Kekerasan yang Dilakukan Suami Terhadap Istri - Muhammad Iqbal Noer Faizi; Rini Fathonah; Aisyah Muda Cemerlang (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze and find the inhibiting factors faced by North Lampung Police investigators in handling domestic violence (KDRT) cases. The research approaches used are normative juridical and empirical juridical The normative juridical approach is carried out by examining laws and regulations related to the handling of domestic violence, such as Law Number 23 of 2004 concerning the Elimination of Domestic Violence. Meanwhile, an empirical juridical approach is carried out through the collection of primary data from interviews with investigators, prosecutors, academics, and non-governmental organizations active in handling domestic violence. Secondary data is obtained from legal literature, official documents, and applicable regulations. The results of the study show that there are several significant obstacles in the process of investigating domestic violence cases. These obstacles include the lack of sensitivity of investigators to the psychological condition of the victim, social pressure and stigma towards the victim that makes reporting low, and limited public understanding of forms of domestic violence, especially non-physical ones such as psychological and economic violence. Internal obstacles also arise from the limitations of supporting facilities such as victim-friendly examination rooms, psychological assistants, and special training for investigators in handling gender-based cases. From the juridical side, the lack of a clear rule regarding the limits of penal mediation in domestic violence cases creates legal uncertainty and opens up space for perpetrators to escape criminal snares through peace that is often impure. In addition, the patriarchal culture that is still strong in society is a structural obstacle in the law enforcement process that favors victims, especially women. Therefore, it is necessary to increase the capacity of investigators through continuous training, the provision of victim-friendly support facilities, widespread legal socialization to the community, and the reformulation of legal policies that are more firm and in favor of victims. Thus, law enforcement of domestic violence cases can be carried out more effectively, fairly, and oriented towards the protection of human rights.